2021
DOI: 10.3389/fgene.2021.688447
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Transcriptome Data to Protein–Protein Interaction Networks of Inflammatory Bowel Diseases Reveals Disease-Specific Subnetworks

Abstract: Inflammatory bowel disease (IBD) is the common name for chronic disorders associated with the inflammation of the gastrointestinal tract. IBD is triggered by environmental factors in genetically susceptible individuals and has a significant number of incidences worldwide. Crohn’s disease (CD) and ulcerative colitis (UC) are the two distinct types of IBD. While involvement in ulcerative colitis is limited to the colon, Crohn’s disease may involve the whole gastrointestinal tract. Although these two disorders di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…APP plays an important role in AD (Maden and Acuner, 2021), which can activate microglia cells in the brain and cause inflammation (Akiyama, 1994). Existing studies have demonstrated the association between AD and IBD (Maden and Acuner, 2021).…”
Section: Validation Of Amyloid Beta Precursor Protein Expression In T...mentioning
confidence: 99%
See 2 more Smart Citations
“…APP plays an important role in AD (Maden and Acuner, 2021), which can activate microglia cells in the brain and cause inflammation (Akiyama, 1994). Existing studies have demonstrated the association between AD and IBD (Maden and Acuner, 2021).…”
Section: Validation Of Amyloid Beta Precursor Protein Expression In T...mentioning
confidence: 99%
“…APP plays an important role in AD (Maden and Acuner, 2021), which can activate microglia cells in the brain and cause inflammation (Akiyama, 1994). Existing studies have demonstrated the association between AD and IBD (Maden and Acuner, 2021). Notably, KEGG and immune infiltration analysis revealed a substantial presence of neutrophils in the lesions of both IBD and AD.…”
Section: Validation Of Amyloid Beta Precursor Protein Expression In T...mentioning
confidence: 99%
See 1 more Smart Citation